Comparative Phytochemical Composition and In vitro Antioxidant Capacity of Aqueous and Methanolic Gmelina arborea Leaf Extracts - Saka, A. A.; Adedeji, O. Y.; Sanusi, G. O.; Osinubi, A. A.; Hamzat, O. A.; Akinwande, A. A.; Banjoko, O. J. (ADAN JOURNAL OF AGRICULTURE, 2026)
This study evaluated and compared the phytochemical composition and in vitro antioxidant potential of aqueous Gmelina arborea leaf extracts (AGALE) and methanolic Gmelina arborea leaf extracts (MGALE). Qualitative and quantitative phytochemical analysis was carried out in both extracts. Both extracts were found to contain key bioactive compounds such as tannins, phenols, flavonoids, alkaloids, and saponins. However, notable differences were observed in their concentration levels: MGALE exhibited higher (P<0.05) contents of phenols (110.0 ± 0.1 mg/100 mL), flavonoids (1378 ± 13.0 mg/100 mL), and alkaloids (425.0 ± 0.2 mg/100 mL), whereas AGALE showed greater levels of tannins (103.88 ± 0.12 mg/100 mL) and saponins (1010 ± 20 mg/100 mL). The antioxidant activities of both extracts were evaluated using 1, 1-diphenyl-2-picryl-hydrazyl assay; (DPPH), 2, 2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid); (ABTS) and the ferric reducing antioxidant power (FRAP) assay. Results showed that MGALE exhibited significantly higher (P<0.05) antioxidant activity, with DPPH (54.89 ± 0.08%) and ABTS (75.93 ± 0.25%) values, compared to AGALE, which recorded 33.92 ± 0.16% and 27.48 ± 0.11%, respectively. Conversely, AGALE exhibited a markedly (P<0.05) superior FRAP: 50.00 ± 0.11% compared to MGALE (12.65 ± 0.03%). The study concludes that both AGALE and MGALE have valuable potential in ruminant nutrition and health, and that the extraction solvent is a key factor influencing the concentration and effectiveness of their bioactive components.